The financial impact of a breast cancer detected within and outside of screening: lessons from the Australian Lifepool cohort - Karinna Saxby; Carolyn Nickson; G. Bruce Mann; Louiza Velentzis; Hannah L. Bromley; Pietro Procopio; Karen Canfell; Dennis Petrie (Elsevier, 2020)
Abstract Objective: To determine the government and out‐of‐pocket community costs (out‐of‐hospital medical services and prescription medicines) associated with screen‐detected and community‐detected cancers (i.e. cancers detected outside of Australia's organised screening program [BreastScreen]). Methods: We analyse administrative data on government‐subsidised medical services and prescription medicines for 568 Victorian women diagnosed with breast cancer or ductal carcinoma in situ (DCIS). Using multivariable regression analysis, we estimate the government and out‐of‐pocket community costs incurred in the three years after diagnosis for screen‐detected cancers and community‐detected cancers. Additionally, we estimate the government costs associated with diagnosis within and outside of BreastScreen. Results: Average government costs for breast cancer diagnosis were similar within and outside of BreastScreen [$808 (lower limit 676; upper limit 940) vs $837 (95%CI 671; 1,003) respectively]; however, women with community‐detected cancers incurred an additional $254 (95%CI 175; 332) out‐of‐pocket. Controlling for differences in known cancer characteristics, compared to screen‐detected cancers, community‐detected breast cancers were associated with an additional $2,622 (95%CI 644; 4,776) in government expenditure in the three years following diagnosis. Adverse cancer characteristics that were more prevalent in community‐detected cancers (high grade, lymph node involvement, HER2 positive receptor status) were associated with increased government and out‐of‐pocket costs. Conclusions: Community‐detected breast cancers were associated with increased government and out‐of‐pocket costs. Implications for public health: These costs should be considered when evaluating current and alternative breast cancer screening strategies.